The Role of Micro, Small and Medium Enterprises (MSMEs) in Alleviating Poverty Caused by Unemployment - Yuwan Ferdiana Ilahi; Munirul Abidin; Vivin Maharani Ekowati; Ceta Indra Lesmana (Jurnal Ekonomi Pembangunan, 2023)
The purpose is To examine the role of MSMEs in overcoming poverty caused by unemployment in West Java. The data used is secondary data taken from the Central Bureau of Statistics (BPS). The analytical method used is Partial Least Square (PLS). The sample selection in this study was determined using the census method. The census method is a method that takes a sample of all districts and cities in West Java. The sample data used are districts and towns in East Java, namely 27 districts/cities. The results of the R-Square test show that the independent variable (unemployment) affects poverty by 68%, while other factors outside the model influence the additional 32%. The unemployment variable can increase MSMEs by 30%, while other factors outside the research model influence the other 70%. The MSME variable can reduce poverty by 67%, while other factors outside the model affect the additional 33%; the results of the significance level test show that unemployment has a direct and significant positive relationship with poverty. Unemployment has a direct and consequential positive relationship with MSMEs. MSMEs have a direct and consequential positive relationship to poverty. Moreover, MSMEs can moderate the relationship between unemployment and poverty.